How to Subvert Democracy: Montesinos in Peru - John McMillan; Pablo Zoido (Center for Economic Studies and ifo Institute (CESifo), 2004)
Which of the democratic checks and balances - opposition parties, the judiciary, a free press -is the most critical? Peru has the full set of democratic institutions. In the 1990s, the secret-police chief Vladimiro Montesinos systematically undermined them all with bribes. We quantify the checks using the bribe prices. Montesinos paid television-channel owners about 100 times what he paid judges and politicians. One single television channel's bribe was four times larger than the total of the opposition politicians' bribes. By revealed preference, the strongest check on the government's power was the news media.
Keywords: 330